2009
DOI: 10.1038/jid.2008.352
|View full text |Cite
|
Sign up to set email alerts
|

Skin Exposure to Weak and Moderate Contact Allergens Induces IFNγ Production by Lymph Node Cells of CD4+ T-Cell-Depleted Mice

Abstract: Allergic contact dermatitis (ACD) is mediated by hapten-specific CD8+ T cells and downregulated by CD4+ T cells. We have recently shown in a model of ACD to weak haptens that priming of IFNgamma-producing CD8+ T cells and the development of skin inflammation could be obtained in mice deficient in CD4+ T cells. Here we show that IFNgamma production by lymph node (LN) cells draining the site of skin sensitization of CD4+ T-cell-deficient mice is a marker of the sensitizing properties of weak haptens. LN cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The idea that immune tolerance rather than ignorance explains the general innocuity of weak haptens is supported both in mouse and human. Indeed, we showed that normal mice do not mount CHS responses to common chemical allergens of fragrance unless they are acutely depleted of Tregs (11). Moreover, studies of nickel allergy best illustrated that a weak sensitizing allergen can activate Tregs, as most healthy control individuals harbor functional allergen-specific and suppressive CD4 + CD25 + Tregs (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that immune tolerance rather than ignorance explains the general innocuity of weak haptens is supported both in mouse and human. Indeed, we showed that normal mice do not mount CHS responses to common chemical allergens of fragrance unless they are acutely depleted of Tregs (11). Moreover, studies of nickel allergy best illustrated that a weak sensitizing allergen can activate Tregs, as most healthy control individuals harbor functional allergen-specific and suppressive CD4 + CD25 + Tregs (12).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that CD4 + CD25 + Foxp3 + Tregs are essential to controlling the development and severity of skin allergy in both mouse models (5,8) and in humans (12). Indeed, allergen-specific Tregs can be detected in allergen-exposed but nonallergic individuals (12) and are likely mandatory for prevention of sensitization, as depletion of Tregs in mouse models allows for development of CHS to otherwise nonsensitizing weak haptens (11). Yet an understanding of how allergen-specific Tregs are generated is still elusive.…”
Section: Cd207 -Ddcs To Lnsmentioning
confidence: 99%
“…Depletion of regulatory CD25 + - or CD4 + -T cells in vivo increases the number of IFN-γ-producing T cells during sensitisation. Likewise the sensitivity of the corresponding in vitro assays can be increased by using systems depleted of CD25 + T cells [187, 188]. …”
Section: Introductionmentioning
confidence: 99%
“…T cells were depleted before sensitization [88][89][90]. In addition sensitive detection methods allow amplification of weak T-cell responses by polyclonal expansion of precursors [63] and the multiparametric analysis of single cells using flow cytometric detection of cell surface markers including those that indicate antigen-specific activation and intracellular cytokines [51,[56][57][58].…”
Section: Resultsmentioning
confidence: 99%